Estabelecimento de metodologia para alimentação de Aedes aegypti (Diptera-Culicidae) em camundongos swiss e avaliação da toxicidade e do efeito residual do óleo essencial de Tagetes minuta L (Asteraceae) em populações de Aedes aegypti Establishment of the feeding methodology of Aedes aegypti (Diptera-Culicidae) in Swiss mice and evaluation of the toxicity and residual effect of essential oil from Tagetes minuta L (Asteraceae), in populations of Aedes aegypti - Waldemir Pereira Lima; Francisco Chiaravalloti Neto; Maria de Lourdes da Graça Macoris; Débora Aparecida Pires de Campos Zuccari; Margareth Regina Dibo (Revista da Sociedade Brasileira de Medicina Tropical, 2009)
Objetivou-se desenvolver um procedimento de alimentação de fêmeas de Aedes aegypti que não cause estresse em camundongo swiss e avaliar a toxicidade e o efeito residual do óleo essencial de Tagetes minuta L (Asteraceae) em populações de Aedes aegypti. Camundongos anestesiados: um observado tempo de sedação e outro colocado em gaiola para alimentação de fêmeas. Óleo essencial, diluído em acetona, foi utilizado em bioensaios para avaliação das concentrações letais em larvas de Bauru, SP e São José do Rio Preto, SP, respectivamente, sensíveis e resistentes ao temephos. Os dados obtidos foram comparados com a cepa Rockefeller-EUA. O procedimento com camundongos foi aprovado. Não houve diferença entre as populações quanto à susceptibilidade a Tagetes minuta e os ensaios demonstraram CL50 de 0,24, 0,25 e 0,21mL L-1 e CL99,9 em 0,35, 0,39 e 0,42mL L-1, respectivamente, para Rockfeller, Bauru e São José do Rio Preto. Não foi observado efeito residual da solução. The objectives here were to develop a procedure for feeding females of Aedes aegypti that does not cause stress in Swiss mice and to evaluate the toxicity and residual effect of essential oil from Tagetes minuta L. (Asteraceae) in Aedes aegypti populations. Two mice were anesthetized: one was used to observe the duration of sedation and the other was placed in a cage to feed the female mosquitoes. Essential oil was diluted in acetone and used in bioassays to assess the lethal concentrations in larvae from the Cities of Bauru (SP) and São José do Rio Preto (SP) that were sensitive and resistant to temephos, respectively. The data obtained were compared with the American Rockefeller strain. The procedure with mice was approved. There was no difference between the populations regarding susceptibility to Tagetes minuta, and the assays showed LC50 of 0.24, 0.25 and 0.21 ml/l and LC99.9 of 0.35, 0.39 and 0.42 ml/l, for Rockefeller, Bauru and São José do Rio Preto, respectively. The solution did not show any residual effect.